Pelatihan Calon Reporter bagi Mahasiswa Jurnalistik UTU dan Mahasiswa UIN Ar-Raniry pada Harian Serambi Indonesia - Muzakkir Muzakkir; Murhaban Murhaban; Teuku Farizal; Al Munawir; Herdi Susanto; Mirza Adia Nova; Desi Maulida; Futri Syam; Raudhatun Nafisah (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2024)
In today's digital age, information advancement has become critical for society's well-being. Misinformation, when disseminated, can have negative impacts and even turn into a disaster for the public. Therefore, it is crucial for reporters and journalists in the media to possess the intelligence to conduct research, analyze, interpret, and deconstruct from a journalistic perspective. This will enable aspiring reporters to effectively utilize media (tools) such as print, electronic, and internet to meet human needs, particularly when navigating the challenges of new media. Therefore, the goal of this training program for aspiring reporters is to equip communication science students with the skills necessary to become creative and innovative writers who can effectively convey information to the public. The benefits of this training are to produce individual reporters who are capable of providing sharp and critical arguments regarding news and able to absorb information from various public channels. A critical attitude towards issues and emerging problems is needed, handled with wisdom and prudence, not easily swayed by negative opinions. The goal is for aspiring reporters to gain a clear understanding of ideas and concepts through precise, thorough writing, and to possess a brilliant conscience towards the perspective of events. This training utilizes lecture and question-answer methods. As a result, aspiring reporters can generate and convey high-quality writing that conveys information or news about the atmosphere or conditions of events, enabling platform users (media) to understand rumors and news that reporters format and disseminate to a broader audience.